Cu(II) Coordination Polymers as Vehicles in the A3 Coupling - Loukopoulos, Edward; Kallitsakis, Michael; Tsoureas, Nikolaos; Abdul-Sada, Alaa; Chilton, Nicholas F.; Lykakis, Ioannis N.; Kostakis, George E. (Inorganic Chemistry, 2017)
A family of benzotriazole based coordination compounds, obtained in two steps and good yields from commercially available materials, formulated as [CuII(L1)2(MeCN)2]·2ClO4·MeCN (1), [CuII(L1)(NO3)2]·MeCN (2), [ZnII(L1)2(H2O)2]·2ClO4·2MeCN (3), [CuII(L1)2Cl2]2 (4), [CuII5(L1)2Cl10] (5), [CuII2(L1)4Br2]·4MeCN·CuII2Br6 (6), [CuII(L1)2(MeCN)2]·2BF4 (7), [CuII(L1)2(CF3SO3)2] (8), [ZnII(L1)2(MeCN)2]·2CF3SO3 (9), [CuII2(L2)4(H2O)2]·4CF3SO3·4Me2CO (10), and [CuII2(L3)4(CF3SO3)2]·2CF3SO3·Me2CO (11), are reported. These air-stable compounds were tested as homogeneous catalysts for the A3 coupling synthesis of propargylamine derivatives from aldehyde, amine, and alkyne under a noninert atmosphere. Fine tuning of the catalyst resulted in a one-dimensional (1D) coordination polymer (CP) (8) with excellent catalytic activity in a wide range of substrates, avoiding any issues that would inhibit its performance.